(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
Maintenance, Repair, and Overhaul (MRO) is a critical industry sector that ensures the optimal performance and safety of aircraft and marine systems through comprehensive servicing, inspection, and repair. This literature review explores the complexities and challenges of MRO management, emphasizing its significance in maintaining airworthiness, operational safety, and compliance with regulations. It examines various risk management techniques, including Failure Mode and Effect Analysis (FMEA) and its extensions, to address equipment failures and enhance maintenance strategies. The review highlights how proactive and systematic approaches, such as risk analysis and Pareto analysis, are used to identify key issues impacting production efficiency and safety. Additionally, it discusses the growing role of advanced organizational practices and interdisciplinary considerations in optimizing maintenance outcomes. The review concludes by introducing the concept of modeling and simulation as valuable tools for improving MRO processes. By leveraging these techniques, organizations can better predict and manage maintenance needs, optimize resource allocation, and enhance overall operational performance.